2001
DOI: 10.1089/10799900152547867
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Treatment Augments Cutaneous Wound Healing in Immunosuppressed Mice

Abstract: It has been postulated that the inflammatory response that occurs after cutaneous wounding is a prerequisite for healing and that inflammatory cytokines, such as interleukin-6 (IL-6) are involved in this process. We showed previously that IL-6-deficient mice display delayed wound healing, which could be reversed by administration of a murine IL-6 expression plasmid or recombinant murine IL-6 (rMuIL-6). In the present study, we observed that delayed cutaneous wound healing, which occurs as a result of glucocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 45 publications
4
58
1
Order By: Relevance
“…However, its role in wound healing appears to be opposite to those of TNF-α or IL-1β. For example, treatment with IL-6 augmented wound healing in immunosuppressed mice (26). In line with this, Lin et al (27) reported delayed wound healing in IL-6-deficient mice.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 82%
“…However, its role in wound healing appears to be opposite to those of TNF-α or IL-1β. For example, treatment with IL-6 augmented wound healing in immunosuppressed mice (26). In line with this, Lin et al (27) reported delayed wound healing in IL-6-deficient mice.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 82%
“…Increased cellular infiltration is followed by severe retinal damage. Interleukin (IL)-6 is a pleiotropic cytokine with a wide spectrum of biological activities in a broad variety of ocular inflammatory diseases and wound healing processes (10)(11)(12). IL-6 is an important mediator in a variety of diseases, including inflammatory, autoimmune and malignant diseases.…”
Section: Ycg063 Inhibits Pseudomonas Aeruginosa Lps-induced Inflammatmentioning
confidence: 99%
“…Previously it was found that cutaneous wound healing in IL-6 gene-deficient mice was significantly slower than that in wild type control mice [134][135][136]. It was found that gene expression enhancement of IL-1, chemokines, adhesion molecules, TGF-β1 and VEGF at the wound sites was significantly reduced in IL-6-deficient mice [136].…”
Section: Safety Profile Of Tocilizumabmentioning
confidence: 99%